2001
DOI: 10.1300/j013v34n03_02
|View full text |Cite
|
Sign up to set email alerts
|

Social Support and Avoidant Coping: Correlates of Depressed Mood During Pregnancy in Minority Women

Abstract: This study suggests that women who perceive less social support satisfaction utilize more avoidant coping strategies and experience greater depression mood. Thus, although these associations are not indicative of a causal relationship, results raise the possibility that women at-risk for depressed mood during pregnancy can be identified by assessing perceived social support and coping styles. Future prospective studies are needed to test the causal relationships among these variables. Clinical interventions to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
1
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 43 publications
5
38
1
3
Order By: Relevance
“…Leithner et al 7 , Hamilton et al 8 , Rudnicki et al 34 and Borcherding et al 35 studied coping strategies of patients following an abnormal screening test result. Durand et al 29 pointed at the important supporting role of partners and doctors in the decision making process whether to undergo amniocentesis.…”
Section: Discussionmentioning
confidence: 99%
“…Leithner et al 7 , Hamilton et al 8 , Rudnicki et al 34 and Borcherding et al 35 studied coping strategies of patients following an abnormal screening test result. Durand et al 29 pointed at the important supporting role of partners and doctors in the decision making process whether to undergo amniocentesis.…”
Section: Discussionmentioning
confidence: 99%
“…O estresse parece estar relacionado à presença de humor deprimido e ansiedade durante a gravidez 17 . O suporte social recebido antes e durante a gestação, principalmente o oferecido pelo cônjuge, parece ser determinante para o bem-estar mental da gestante, visto que sua ausência tem sido associada à manifestação de sintomas depressivos na gravidez 67,72,78,[83][84][85][86][87] . A percepção do suporte social recebido pelo marido está relacionada, inclusive, à prevalência de depressão após o parto 88 .…”
Section: Discussionunclassified
“…Empirical studies found avoidant coping as an associated outcome of negative event (Holahan & Moos, 1987), as well as a predictor of poor psychosocial adjustment over a long period of time including depressive symptoms (Simoni & Ng, 2000), overall psychological distress (Steel, Sanna, Hammond, Whipple, & Cross, 2004), and posttraumatic stress disorder (Street, Gibson, & Holohan, 2005). Further, avoidant coping strategies are typically ineffective for eliciting social support or engaging in problem solving activities (Rudnicki, Graham, Habboushe, & Ross, 2001). Previous studies investigating the mediational role of avoidant coping between childhood trauma and outcomes in adulthood have produced mixed results: Some (Merrill, Thomsen, Sinclair, Gold, & Milner, 2001;Runtz & Schallow, 1997) reported the mediational effects of avoidant coping, whereas others (Steel et al, 2004) found no such evidence.…”
Section: S T R E S S a N D C O P I N G T H E O R Ymentioning
confidence: 99%